Milwaukee Police Department retirees: cardiovascular disease risk and morbidity among aging law enforcement officers. - Ramey SL; Downing NR; Franke WD (AAOHN Journal, 2009)
This study explored the self-reported prevalence of cardiovascular disease (CVD) and accompanying risk factors among 165 male retirees 43 years and older (M = 56.2, SD = 7.1) from the Milwaukee Police Department (MPD) compared to 671 individuals of similar age and income who responded to the 2005 Wisconsin Behavioral Risk Factor Surveillance System (BRFSS). CVD and other risk factors were more prevalent in the MPD retirees than the general population (CVD 15.2% vs. 9.5%, p = .036; hypertension 51.5% vs. 36.2%, p = .001; hypercholesterolemia 62.4% vs. 44.4%, p = .001; overweight and obesity 85.1% vs. 74.7%, p = .005). In addition, other factors associated with CVD prevalence included working in law enforcement (odds ratio = 1.70; 95% confidence interval = 1.03 to 2.79). Results suggest an association between employment in law enforcement and an increase in CVD morbidity.